PENYULUHAN MASYARAKAT DESA SADAR COVID 19 MELALUI POSTER - Kayyis, Rahmatika; Rosida, Ainur; Khasanah, Binti Anisaul (Abdimas Siliwangi, 2021)
The Covid 19 pandemic has made all people aware of the importance of maintaining personal hygiene to fight the spread of the virus. The government readily appealed to Indonesian citizens to always wash their hands, wear masks, and keep their distance. However, in remote areas, the government's appeal is not on target. Based on the survey results during the implementation of the 2020/2021 KKND UMPRI, there were still many residents who were ignorant and did not know the appeal. Therefore the aim of this service is to provide information to the village community about awareness about COVID 19 through the media of posters. The method of implementing this service activity includes: surveys, creating posters, and poster publication. The impact of this activity is to increase public awareness of the government's appeal against COVID 19 which is measured by: (1) creating awareness of community members about washing hands, using masks, and maintaining distance; (2) increasing community knowledge about the symptoms, dangers and handling of COVID 19; and (3) increasing public knowledge about prevention measures for transmission of COVID 19.